The Current Status of Strategic Planning at Jouf University in the Kingdom of Saudi Arabia from Teaching Staff’s Perspective - Abouelfadl Hegazy, Ahmad; Hasan Arif, Osama (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at recognizing the current status of strategic planning at Jouf University in the Kingdom of Saudi Arabia from the teaching staff’s perspective. The sample consisted of 99 members. The researcher used the descriptive analytical method, using the survey as a main tool for answering the research queries. The survey included two axes: “the quality of strategic planning,” which contained 23 phrases, and “the implementation and follow-up on the strategic level,” which contained 12 phrases. The most important result was that the two axes of the study were of a very high degree. Also, it revealed that there are no differences attributed to the variables of the study sample.